Metformin Reverses Hashimoto’s Thyroiditis by Regulating Key Immune Events - Jia, Xi; Zhai, Tianyu; Qu, Chunjie; Ye, Jianjun; Zhao, Jing; Liu, Xuerong; Zhang, Jin-an; Qian, Qiaohui (Frontiers in Cell and Developmental Biology, 2021)
Background: Hashimoto's thyroiditis (HT) is a common autoimmune disease characterized by high levels of thyroid peroxidase antibody (TPOAb) and thyroid globulin antibody (TgAb) as well as infiltration of lymphocytes in thyroid. In recent years, metformin has been proven to be effective in a variety of autoimmune diseases, such as systemic lupus erythematosus, rheumatoid arthritis and multiple sclerosis. Methods: This study systematically explored the therapeutic effect of metformin on HT and its underlying mechanism by comprehensively utilizing methods including animal model, in vitro cell culture and differentiation, mRNA sequencing and 16S rRNA sequencing. Findings: We found that metformin indeed had a therapeutic effect on mice with HT mainly by reducing TgAb and lymphocyte infiltration in thyroid tissue. In addition, metformin also significantly suppressed the number and function of Th17 cells and M1 macrophages polarization in HT mice. Furthermore, metformin can inhibit the differentiation and function of Th17 in vitro. The results of mRNA sequencing of thyroid tissue illustrated that the therapeutic effect of metformin on HT was mainly achieved by regulating immune pathways. 16S RNA sequencing of the intestinal flora found that the intestinal flora of HT mice differs significantly from that of the normal mice and also were altered by metformin treatment. Interpretation: These experiments provided a preliminary theoretical basis for the clinical application of metformin in the treatment of HT.